COVID‐19 convalescent plasma: Evolving strategies for serological screening in France. Issue 4 (12th December 2021) - Gallian, Pierre; Le Cam, Sophie; Brisbarre, Nadège; Pastorino, Boris; Amroun, Abdennour; Malard, Lucile; de Lamballerie, Xavier; Bliem, Cathy; Richard, Pascale; Morel, Pascal; Tiberghien, Pierre
Abstract: Quantitation of anti‐SARS‐CoV‐2 (severe acute respiratory syndrome coronavirus 2) neutralizing antibodies (Nabs) is a key parameter in determining the effective dose for treatment with COVID‐19 convalescent plasma (CCP). Interpretation of results from clinical trials conducted worldwide requires comparison of Nabs titres obtained from different methods. As virus neutralization tests (VNTs) are not standardized scalable or commercially available, strategies based on intensity of ELISA (Enzyme Linked Immunosorbent Assay) or chemiluminescent binding serological tests were implemented to allow comparisons and establish criteria for determining 'high‐titres' of anti‐SARS‐CoV‐2 antibodies (Abs). To this end, the FDA (Food and Drug Administration) has proposed criteria to define high‐titre plasmas using different serological assays, including the one used in France for the CCP SARS‐CoV‐2 Abs screening (Euroimmun anti‐S1 IgG). A retrospective study revealed that when using the FDA criteria (ELISA signal‐to‐cut‐off [S/C ratio] ≥3.5), 91% of CCP had Nabs titres ≥40 as assessed with an in‐house VNT. French strategy to ensure sufficient stocks of CCP of increasing titre has evolved over time. Recently, we improved our strategy by collecting only plasma from vaccinated convalescent donors as we confirmed that the mean IgG antibody level (ELISA S/C ratio) was significantly higher in plasma from vaccinated convalescent donors compared to donations from unvaccinated convalescent donors: 9.31 (CI 95%: 8.46–10.16) versus 3.22 (CI 95%: 3.05–3.39) ( p  < 0.001).